Transmission and Reflection Mode Macroscopic X-ray Powder Diffraction Imaging for the Noninvasive Visualization of Paint Degradation in Still Life Paintings by Jan Davidsz. de Heem - Vanmeert, Frederik; de Keyser, Nouchka; van Loon, Annelies; Klaassen, Lizet; Noble, Petria; Janssens, Koen (Analytical chemistry (Washington), 2019)
The use of noninvasive chemical imaging techniques is becoming more widespread for the study of cultural heritage artifacts. Recently a mobile instrument for macroscopic X-ray powder diffraction (MA-XRPD) scanning was developed, which is capable of visualizing the distribution of crystalline (pigment) phases in quasi-flat-painted artifacts. In this study, MA-XRPD is used in both transmission and reflection mode for the analysis of three 17th century still life paintings, two paintings by Jan Davidsz. de Heem (1606-1684) and one copy painting after De Heem by an unknown artist. MA-XRPD allowed to reveal and map the presence of in situ-formed alteration products. In the works examined, two rare lead arsenate minerals, schultenite (PbHAsO ) and mimetite (Pb (AsO ) Cl), were encountered, both at and below the paint surface; they are considered to be degradation products of the pigments realgar (α-As S ) and orpiment (As S ). In transmission mode, the depletion of lead white, present in the (second) ground layer, could be seen, illustrating the intrusive nature of this degradation process. In reflection mode, several sulfate salts, palmierite (K Pb(SO ) ), syngenite (K Ca(SO ) ·H O), and gypsum (CaSO .2H O), could be detected, in particular, at the (top) surface of the copy painting. Estimates for the information depth and sensitivity of both transmission and reflection mode MA-XRPD for various pigments have been made. The possibility of MA-XRPD to allow for noninvasive identification and visualization of alteration products is considered a significant advantage and unique feature of this method. MA-XRPD can thus provide highly relevant information for assessing the conservation state of artworks and could guide possible future restoration treatments.